2020
DOI: 10.17520/biods.2020134
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of wildlife consumption and trade during the COVID-19 outbreak

Abstract: The COVID-19 pandemic has drawn great attention to the potential public health risks associated with the consumption and trade of wildlife. To inform legislative revision and policy changes, we conducted a web-based survey of the general public, attracting 74,040 responses. The survey examined public support for revising legislation and policy related to wildlife consumption and trade management. The results and analysis revealed: (1) The overwhelming majority (> 90%) of constituents supported more stringent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The findings somewhat align with a recent study regarding Chinese public opinions on revising legislation and policy related to wildlife consumption and trade management. Due to the perceived threat of the Covid-19 outbreak, more than 90% of the respondents support more stringent policies and legislation on wildlife trade, consumption, and commercial exhibitions [59]. Shi et al also note that the support is more prevalent among educated and urban people.…”
Section: Discussionmentioning
confidence: 99%
“…The findings somewhat align with a recent study regarding Chinese public opinions on revising legislation and policy related to wildlife consumption and trade management. Due to the perceived threat of the Covid-19 outbreak, more than 90% of the respondents support more stringent policies and legislation on wildlife trade, consumption, and commercial exhibitions [59]. Shi et al also note that the support is more prevalent among educated and urban people.…”
Section: Discussionmentioning
confidence: 99%
“…Observed attitude changes toward the trade in wildlife among the Chinese population (Shi et al, 2020 ) have been seen as a positive indicator of both reduced consumption and disease risk. However, the continued post-SARS wildlife trade, together with evidence from this study regarding changes in public knowledge over time, indicates that a general emphasis on the threat is inadequate to sustain public awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The Huanan market in Wuhan was immediately closed following the identification of its association with COVID-19, and a national ban on the consumption of terrestrial wildlife was enacted (Xinhua News Agency, February 24, 2020b ). Following the emergence of COVID-19, a survey of 74,040 Chinese citizens found that more than 90% of respondents supported more stringent wildlife trade policies, and some respondents expressed a willingness to stop consuming wildlife (Shi et al 2020 ). However, similar changes in attitudes toward the wildlife trade and conservation were observed in China before and after the SARS outbreak (Yang et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on practice survey, the overwhelming majorities (>90%) of the respondents in the survey support more stringent policy and legislation on wildlife consumption, trade, and commercial exhibitions. The comprehensive prohibition on illegal wildlife trade and the elimination of abusive wild animals eating habits has a wide public base [ 24 ]. This means that the existing wild animals consumption groups tend to stop consuming after the COVID-19, and the future wild animals consumption market will be greatly reduced, the wide public support determines the applicability and effectiveness of wild animal legislation.…”
mentioning
confidence: 99%